Pengaruh Kesadaran Wajib Pajak Dan Penggunaan E-tax Service Terhadap Kepatuhan Wajib Pajak Pada Kpp Pratama Bontang - Risna, Risna; Misran, Misran; Gafur, Abdul; Leo, Muarif; Virginia, Winda Ayu; Alimuddin, Irmawati; Pudo, Fajar (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2025)
This study aims to determine the effect of taxpayer awareness and the use of e-Tax services including (e-Registration, e-SPT, e-Filling, e-Billing), at the Bontang Pratama Tax Office. The research method used is a quantitative method. The data used in this study are primary data in the form of interviews, questionnaires and secondary data in the form of literature studies. The object of research in this study is individual taxpayers registered at the Bontang Pratama Tax Service Office. The population of this study is all individual taxpayers who carry out business activities or freelance work at the Bontang Pratama Tax Office who report SPT electronically (e-Filling), with a total of 15,036 WPOP. The sampling method used is Purposive Sampling of 100 respondents. The analysis method used is multiple linear regression with the help of IBM SPSS Statistics 25 software. The results of this study indicate that: (1) Taxpayer awareness has a positive effect on taxpayer compliance at the Bontang Pratama Tax Office. (2) The use of e-Registration has a positive effect on taxpayer compliance at the Bontang Pratama Tax Office. (3) The use of e-SPT has a positive effect on taxpayer compliance at KPP Pratama Bontang. (4) The use of e-Filling has a positive effect on taxpayer compliance at KPP Pratama Bontang. (5) The use of e-Billing has a positive effect on taxpayer compliance at KPP Pratama Bontang. (6) Taxpayer awareness and the use of e-tax services including e-Registration, e-SPT, e-Filling, and e-Billing have a positive effect on taxpayer compliance at KPP Pratama Bontang.